Aprendendo por música - Silva, Rosivam Rodrigues da; Souza , AmandaVenancio da Silva de; Oliveira , Edilene deJesus Cardoso; Polli, Auro Gomes; Polli , Vanderley Gomes; Silva, Joaquim Manoel da; Borges, Marlene Soares da Silva; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf